Short Note: New Carbonate Outcrops in the Badung Peninsula, Southern Bali - Herman Darman (Ikatan Ahli Geologi Indonesia, 2016)
Recent excavations, facility constructions and road cuts in the Badung Peninsula, southern Bali have provided additional exposure to the Selatan Limestone Formation. This short note highlights interesting features of the newly discovered outcrops, which are situated near popular touristic destinations including the beaches of the south coast and Garuda Wisnu Kencana Cultural Park.Although the geology is relatively simple, the varying facies in the outcrops indicate a range of depositional processes. Overall, the limestone beds are flat. The dips of the layers are less than 10° at different directions. The limestones exposed at the observation locations consist of various types of limestones, which are essentially dominated by mudstone and packstone. Homogenous grains, classified as calcarenite to calcirudite, are also found abundant in several other units.